(untitled) (Praxis Educativa, 2012)
Myth as a didactic resource was the fundamental organizing idea for the teaching of Civic Education in Republica del Peru Institute, founded in 1985 in Parera, La Pampa. The main goal of such institution, in direct connection with the university course of Didactics, UNLPam, was focused on educating autonomous individuals capable of social cooperation. The task involved a tracking evaluation which became the subject of several publications and of a curricular evaluation captured by a Master dissertation that verified the political commitment and active insertion of the Institute’s graduates in the community. Encouraged by the success obtained and with the aim of favoring the use of narrative as a didactic strategy, we committed ourselves to an in-depth analysis of the myth’s central theme and its symbols. The selected examples attempt to facilitate the access to the world of mythical narrative, recovering its huge educational potential.